1999
DOI: 10.5032/jae.1999.01057
|View full text |Cite
|
Sign up to set email alerts
|

A Faculty Assessment Of The Academic Rigor Of On- And Off-Campus Courses In Agriculture

Abstract: The purpose of this study was to compare college of agriculture teachingfaculty members 'perceptions of the academic rigor of on-campus and off-campus courses. The population included 262 faculty members with teaching responsibilities or with teaching experience in the College of Agriculture at Iowa State University. All members of the population were surveyed and the response rate was 54.2%. Exploratory factor analysis was used to identify factors underlying college of agriculture teaching faculty members , p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 9 publications
(7 reference statements)
1
41
0
Order By: Relevance
“…Instructors were perceived to have facilitated fewer discussions and created less of a community in online courses. This finding is reinforced by other research conducted to compare the levels of quality in on-and off-campus courses in agriculture (Miller & Shih, 1999).…”
Section: Social Interactionsupporting
confidence: 63%
See 2 more Smart Citations
“…Instructors were perceived to have facilitated fewer discussions and created less of a community in online courses. This finding is reinforced by other research conducted to compare the levels of quality in on-and off-campus courses in agriculture (Miller & Shih, 1999).…”
Section: Social Interactionsupporting
confidence: 63%
“…In both the current study and Miller & Shih (1999), students found instructors to be more available in on-campus courses.…”
Section: Social Interactionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interpretations by college faculty of academic rigor captured by these authors included the promotion of critical thinking, high instructional standards and expectations, a focus more on the learning process than the product, cognitive development of students, high student involvement in learning, and pushing students beyond their comfort level. Miller and Shih (1999) sought to define factors underlying faculty perceptions of academic rigor and identified active participation in the learning process by students, exertion of effort by students, and achievement of higher levels of cognitive learning in Bloom's taxonomy (1956).…”
Section: Academic Challenge and Related Issuesmentioning
confidence: 99%
“…Agriculture professional adult students have the same work, family and social commitments and study characteristics as other adult distance education students (G. Miller, 1997). G. Miller and Shih (1999) reported faculty perceptions that "off-campus students were more eager to learn than on-campus students, brought considerable amounts of experience to their courses, and expected to be able to apply the information immediately" (p. 52).…”
Section: Distance Education Participants and Their Motivesmentioning
confidence: 99%